2022
DOI: 10.4314/vulnew.v80i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Death of a Himalayan Vulture in South India highlights the potential threat of power infrastructure

Abstract: No Abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Road transect surveys showed the presence of all four vulture species present in the area: G. bengalensis, G. indicus, S. calvus and N. percnopterus. However, it was not possible to record any vagrant species during the entire 36 months of survey, even though there were reports of a possible electrocution death of the Himalayan griffon vulture (Manigandan et al 2021b). Even though the encounter rate decreased from 2019 to 2021 (from 1.23 to 0.96 individuals per km) in the study area, G. bengalensis maintained the largest population throughout the study.…”
Section: Neophron Percnopterusmentioning
confidence: 91%
“…Road transect surveys showed the presence of all four vulture species present in the area: G. bengalensis, G. indicus, S. calvus and N. percnopterus. However, it was not possible to record any vagrant species during the entire 36 months of survey, even though there were reports of a possible electrocution death of the Himalayan griffon vulture (Manigandan et al 2021b). Even though the encounter rate decreased from 2019 to 2021 (from 1.23 to 0.96 individuals per km) in the study area, G. bengalensis maintained the largest population throughout the study.…”
Section: Neophron Percnopterusmentioning
confidence: 91%
“…Interestingly, the fatality of a Himalayan Griffon Vulture was observed under powerlines, apparently a result of electrocution in NBR (Manigandan et al 2021) with a burning smell of tissues reported although no tissue testing was done due to a lack of facilities.…”
Section: Evidence Of Other Threatsmentioning
confidence: 99%
“…Inadvertent poisoning is another serious risk to vultures that has not gotten much attention from scientific research. The intentional poisoning of carcasses as retaliation (Harris 2013) and the construction of electrical infrastructure that can electrocute birds (Manigandan et al 2021) have resulted in a notable loss of vultures.…”
Section: Introductionmentioning
confidence: 99%